The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0099323
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Autoantibodies and Connective Tissue Diseases in Chinese Patients with Optic Neuritis

Abstract: BackgroundOptic neuritis (ON) is often associated with other clinical or serological markers of connective tissue diseases (CTDs). To date, the effects of autoantibodies on ON are not clear.PurposeTo assess the prevalence, clinical patterns, and short outcomes of autoantibodies and Sjögren’s syndrome (SS) involvement in Chinese ON patients and evaluate the relationship between ON, including their subtypes, and autoantibodies.MethodsA total of 190 ON patients were divided into recurrent ON (RON), bilateral ON (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
(49 reference statements)
3
8
0
Order By: Relevance
“…A previous study by the present authors also found that AQP4‐IgG sero‐positive ON patients suffered more frequently from recurrent and bilateral ON (Li et al. ). But the prevalence of simultaneous bilateral ON, whether as a present symptom or as a clinical characteristic of already demonstrated NMO, has not been investigated in detail.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…A previous study by the present authors also found that AQP4‐IgG sero‐positive ON patients suffered more frequently from recurrent and bilateral ON (Li et al. ). But the prevalence of simultaneous bilateral ON, whether as a present symptom or as a clinical characteristic of already demonstrated NMO, has not been investigated in detail.…”
Section: Introductionsupporting
confidence: 80%
“…; Li et al. ), providing further support to the hypothesis that simultaneous bilateral ON is more closely related to NMO. Visual acuity (VA) of <0.1 during acute ON attacks was not significantly different between the bilateral and unilateral groups.…”
Section: Discussionsupporting
confidence: 53%
“…Serum and CSF were collected from all patients for NMO-IgG testing. The presence of NMO-IgG was analysed by both commercial enzyme-linked immunosorbent assays (ELISA) kits and extracellular live cell-staining immunofluorescence technique using transiently transfected AQP4-expressing cells, as described in our previous reports (Li et al 2014(Li et al , 2015. All patients underwent a comprehensive ophthalmic examination and standardized treatments.…”
Section: Nmo-igg Testing and Visual Measurementsmentioning
confidence: 99%
“…We also excluded those who had retinal lesions or other causative ocular diseases or had the presence of significant refractive errors (3D of spherical equivalent refraction or 2D of astigmatism), intraocular pressure of 21 mmHg higher, glaucoma, retinal disease, a history of media opacification, ocular pathologies affecting the cornea, lens, or vitreous or laser therapy. Patients with the hepatitis viral infection, human immunodeficiency virus (HIV) infection, syphilitics, lymphoma, graft-versushost disease, lymphoma, human T-lymphotropic virus Type I, or previous head or neck radiation were also excluded [17]. We also excluded the patients who had taken corticosteroids when they collected blood samples for the measurements of AQP4-Ab.…”
Section: Patientsmentioning
confidence: 99%